Negative regulation of filamentous growth in Candida albicans by Dig1p. Issue 5 (21st July 2017) - Regan, Hannah; Scaduto, Christine M.; Hirakawa, Matthew P.; Gunsalus, Kearney; Correia‐Mesquita, Tuana Oliveira; Sun, Yuan; Chen, Yaolin; Kumamoto, Carol A.; Bennett, Richard J.; Whiteway, Malcolm
Summary: Transcriptional regulation involves both positive and negative regulatory elements. The Dig1 negative regulators are part of a fungal‐specific module that includes a transcription factor (a Ste12 family member) and a Dig1 family member. In Saccharomyces cerevisiae, the post‐genome‐duplication Dig1/Dig2 proteins regulate MAP kinase controlled signalling pathways involved in mating and filamentous growth. We have identified the single Dig1 orthologue in the fungal pathogen Candida albicans . Genetic studies and transcriptional profiling experiments show that this single protein is implicated in the regulation of MAP kinase‐controlled processes involved in mating, filamentous growth and biofilm formation, and also influences cAMP‐regulated processes. This suggests that the multiple cellular roles of the Dig1 protein are ancestral and predate the sub‐functionalization apparent in S. cerevisiae after the genome duplication. Intriguingly, even though loss of Dig1 function in C. albicans enhances filamentous growth and biofilm formation, colonization of the murine gastrointestinal tract is reduced in the mutant. The complexity of the processes influenced by Dig1 in C. albicans, and the observation that Dig1 is one of the few regulatory proteins that were retained in the duplicated state after the whole genome duplication event in yeast, emphasizes the important role of these negative regulators in fungal transcriptional control. Abstract : The Dig1 protein of Candida albicans is a negative regulator of various signalling pathways including those for mating, invasion and biofilm formation. The influence of Dig1 on these pathways is primarily mediated through the transcription factors Cph1, Efg1 and Tec1, but the influence of these factors on each of the processes varies significantly, with Cph1 being primarily important for mating, Tec1 for biofilms and invasion and Efg1 for invasion.